Purification, characterization and evaluation of the differential expression of proteases produced by Pseudomonas fluorescens - Alves, Maura Pinheiro (2017)
The milk contaminating psychrotrophic bacteria produce thermo resistant proteases that hydrolyze milk caseins, resulting in loss of milk quality and yield of dairy products. Studies involving the characterization of these enzymes and the knowledge about the conditions that influence their production and activity are essential for preventing these problems. This work aimed to understand the activity and production of the extracellular protease produced by Pseudomonas fluorescens 07A strain. This enzyme showed to be a metalloprotease inhibited by Cu 2+ , Ni 2+ , Zn 2+ , Hg 2+ , Fe 2+ and Mg 2+ , but induced by Mn 2+ and has a molar mass of 49,486 kDa. Partial sequencing of the proteic structure of this enzyme by mass spectrometry allowed the identification of the gene that encodes this protein in the genome of P. fluorescens 07A. The enzyme has 477 amino acids and highly conserved Ca 2+ and Zn 2+ -binding domains, indicating that Ca 2+ , the main ion in milk, is also a cofactor of this enzyme. The enzyme activity is maximum at 37 °C and pH 7.5, b ut it maintains more than 40% activity when subjected to 100 °C for 5 min in ideal medi um and only 14 to 30% in milder heat treatments, which may cause significant problems in the conditions normally used for the processing and storage of milk and dairy products. Low relative expression of protease was observed after 12 h of incubation at 25 °C, when the bacteria is in logarithmic growth phase, compared to its expression in refrigeration temperatures of 4 and 10 °C, when the bacteria is still in lag p hase. Protease production significantly increased (P <0.05) after 24 h at 25 °C and remained constant up to 48 h, when the bacteria remained at stationary phase, indicating that this enzyme could be produced as an adaptive strategy of the bacteria. The casein fractions of reconstituted skim milk were completely degraded as by P. fluorescens 07A, the purified protease or the bacterial extract within seven days of incubation at 25 °C, and to a lesser extent at 10 °C for milk ino culated with the bacteria. Heat treatment at 90 °C for 5 min inactivated the purified enzym e and inhibited its activity in the bacterial extract. This work allowed understanding the biochemical and biological characteristics of the extracellular protease produced of P. fluorescens 07A strain, as well as the conditions that influence its production and activity in milk. These results can help the dairy industry in the search for alternatives for the processing of dairy products to control production and activity of these proteases in milk.